The equation of a circle is written as (x-h)^2 +(y-k)^2 = r^2
h is the x value of the center and k is the y value of the center and r is the radius.
Replace h, k and r with the given information:
(x- -7)^2 + (y - -6)^2 = 4^2
Simplify:
(x+7)^2 + (y+6)^2 = 16
7+3x-12x=3x+1
We will first make all the numbers which have x in go to the left.
So 7+3x-12x-3x, we make the 3x negative since to make it move it needs to change.
Then we will make all the sevens go to the right, so 3x-12x-3x=1-7.
So now it is much easier to figure out.
-12x=-6
Answer:
use a calculator
Step-by-step explanation:
there for question b
Answer:
this is not a real math equation.
Step-by-step explanation: